Optimization of the cultural conditions to enhance lipase production by environmental bacteria - Hameed, Zainab Qais; Alyousif, Nassir Abdullah (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2025)
The production of lipase enzymes has played an essential role in biotechnology since they are used in various environmental applications, including oil pollution treatment. The present study aims to increase the production of lipase enzymes by optimizing nutritional and environmental factors from bacteria isolated from the soil and water from different sites in Basrah province. Seven bacterial isolates out of the fifty that showed positive results in the primary screening exhibited the highest activity in the secondary screening. These isolates belong to the species including Bacillus subtilis strain QD517, Bacillus velezensis strain Bac104, Bacillus subtilis strain PK9, Bacillus cereus strain RB1, Enterobacter cloacae strain YY-2, Bacillus subtilis strain SPA N1, and Bacillus velezensis strain FJ23. The values of lipase enzyme activities of the seven isolates under normal cultivation conditions were 49 U/ml, 28 U/ml, 24 U/ml, 23 U/ml, 23 U/ml, 18 U/ml, and 18 U/ml, respectively. Nutritional and environmental factors including carbon sources, nitrogen sources, phosphorus sources, temperature, pH, and incubation period were examined in this study to increase lipase enzyme activity. The optimal environmental and nutritional conditions were 37 °C, a pH of 7, sunflower oil as the best carbon source, peptone as the best nitrogen source, NH₄H₂PO₄ as the best phosphorus supply and four days as the optimum period of incubation. The maximum lipase activity values for the seven bacterial isolates under optimal conditions were 89 U/ml, 91 U/ml, 86 U/ml, 92 U/ml, 88 U/ml, 88 U/ml, and 89 U/ml, respectively for the bacterial isolates of Bacillus velezensis strain Bac104, Bacillus subtilis strain PK9, Bacillus cereus strain RB1, Bacillus subtilis strain QD517, Bacillus subtilis strain SPA N1, Bacillus velezensis strain FJ23, and Enterobacter cloacae strain YY-2.